Resource allocation strategy of low earth orbit satellite oriented to user transmission difference - Fatang CHEN; Miao HUANG; Yufeng JIN (Tongxin xuebao)
In the low earth orbit (LEO) uplink communication scenario, aiming at the different needs of different users for high capacity transmission (HCT) and high reliability transmission (HRT), the spectrum of two users with different needs was shared, a resource allocation model for maximizing the total capacity of HCT users under the constraint of HRT users was established, and the user power and channel resources were optimized.Based on the statistical characteristics of channel fading, the power allocation was carried out to deal with the uncertainty challenge caused by the randomness of channel fading.On the basis of power allocation, the Hungarian algorithm was used to pair users to share the same channel.In order to improve the fairness of HCT users, the maximization of minimum ergodic capacity was included in the optimization goal, and a balance matrix was introduced to solve the problem based on the existing algorithms.Simulation results show that the total capacity of HCT users of the proposed algorithm is higher than that of other algorithms under the same HRT user outage probability, and the improved algorithm also has a significant effect on improving the fairness and robustness of HCT users.